Situation of air pollution in Metropolitan Lima and Callao - Iglesias León, Silvia (2001)
This article shows the results of the research project that included air quality monitoring at eight stations located in different districts of Lima and Callao in 2000. Air quality monitoring basically consisted of measuring material Particulate, lead and arsenic in PM10 in three seasons of the year, late summer, winter and spring. The concentrations at the end of the summer were higher than those of the rest of the year, mainly due to the weather conditions. The monitoring station, located in the Comas district, had a PM10 concentration of 240 mg / m3. A concentration of 1,601 lead in PM10 was found at the Callao monitoring station.